The effect of the Covid-19 pandemic on patient visits to the emergency department and hospitalizations in medical wards in an Israeli medical center - Yael Frenkel Nir; Yuval Levy; Amit Gutkind; Ehud Grossman (BMC, 2021)
Abstract Background The Covid-19 pandemic began in Israel on February 2020. Between February and October 2020, 2 periods of lockdown were imposed on Israeli population. Objective To assess the effect of the Covid-19 pandemic on visits to the emergency department (ED) and on hospitalizations in medical wards in Israel's Chaim Sheba Medical Center, and to compare the effect during the first and second lockdowns. Methods Data regarding the number of visits of non-Covid-19 patients to the ED and the number of admissions to the medical wards, were extracted from the computerized system of the hospital. Data were analyzed for patients' characteristics, length of stay in the medical wards, in hospital mortality and the rate of 7 and 30 days re-hospitalization, and compared to the same period during 2019. Results Total visits to the Sheba ED during March-October decreased by 18.5%. The most dramatic decrease occurred during the first lockdown. The number of patients admitted to the Sheba medical wards decreased by 28% (P < 0.05). The length of stay decreased from 3.69 days during 2019 to 3.42 days during 2020 (P < 0.01). The most pronounced decrease in the length of stay was observed during the second month of the first lockdown. During the pandemic, hospitalized patients at Sheba were older and were less likely to be males. The in-hospital absolute non-COVID mortality decreased from 913 to 858 respectively. Conclusions The Covid-19 crisis emphasizes the role of medical wards in the care of complex patients. Medical wards in Israel were at the frontline of Israel's battle against this pandemic, while continuing to treat very complex non-Covid patients. To avoid burnout of the medical staff who treat very intensively complex patients, we believe these wards should be strengthen with specialists having expertise in treating these patients. Due to our insights, the Sheba medical Center is now redesigning the concept of how intensive care beds should be managed in a big tertiary center.